High-quality implementation for a continuous-in-time financial API in C# - Chakkour, Tarik (Frontiers in Computer Science, 2024)
In this paper, we proposed high-quality Application Programming Interface (API) to implement the continuous-in-time financial model. Our proposal uses mathematical modeling consisting of some objects as measures and fields. It is suitable to develop this API in C# to provide professionally the requirement quality in programming language. This also integrates demands, codes, and verification in the system development life cycle. The advantages are aimed at increasing the structuring and readability. The presented work gives an overview of the API and its design by describing the implementation concerning the data structures and algorithms. These algorithms are based on using the Task Parallel Library (TPL) that makes the API easier and more fruitful for data parallel to benefit from the advantages provided by the .NET Framework.